Ekstremni športi - Kavčič, Matic (Družboslovne razprave, 2006)
The importance of sport as an element of our lives is growing in contemporary society. Even more visible is the growth in participation in extreme sports. This article introduces the sociological dimensions of risk and danger when participating in extreme sports in these times of the risk society . Although individual risk-taking is often seen as an inborn personality characteristic this article tries to set the social aspects and meanings of taking risks in extreme sports in a wider social context. The findings show that, due to a high level of differentiation, pluralisation and individualisation, modern societies are establishing the conditions for a crisis of meaning. In these conditions, extreme sports are comprehended as ćintermediary structures', a way of encountering the confusing contemporary circumstances. Participating in extreme sports is about the personal generation of meaning through risks and its feedback in everyday life.
Keywords: sport; šport; družba tveganja; ekstremni športi; nevarnosti; sociološki vidik